Customers satisfaction on mobile telecommunication in Kuching: case study on CMS Cement employees / Veronica Meling Akeng - Akeng, Veronica Meling (2017)
The purpose of this study is to determine factors that affect customers’ satisfaction on mobile telecommunication in Kuching, a case study on CMS employees. Factors related to services like call quality, network coverage, signal strength, internet service, price fairness, customer support service and value-added services are the most significant in determining satisfaction and likelihood to stay or switch to other service provider and also possibility for recommendation to a new user. As mobile telecommunication service has been a part of modem life necessity, the needs to improve the whole service is crucial since almost all daily transactions be it for personal purposes, businesses or government run services depend so much on the efficiency of telecommunication service. With the independent variables; i) call quality,network coverage, signal strength ii) internet service iii) price fairness iv) customer support service and v) value-added services, the researcher will be able to test the significant relationship between the variables and the findings from this study can suggest the determinants in predicting customer loyalty.